2023
DOI: 10.1007/s10238-023-01161-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the intestinal microbiome and metabolome in women with rheumatoid arthritis

Abstract: Objectives: Rheumatoid arthritis (RA) is more common in women, and many reports of sex differences have been reported in various aspects of RA. However, there has been a lack of speci c research on women's gut ora. To assess the association between the gut ora and RA patients, this study combined the microbiome with metabolomics.Methods: Fecal samples from RA patients and healthy controls were collected for 16S rRNA sequencing.Nontargeted liquid chromatography-mass spectrometry was used to detect metabolites i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Additionally, a more severe disease course and unfavorable prognosis have been consistently associated with the female gender ( Finckh et al, 2022 ). Despite extensive research on gender-related distinctions in RA ( Di Florio et al, 2020 ; Favalli et al, 2019 ), Yun et al (2023) recently highlighted a lack of studies specifically examining the gut microbiome characteristics in females, elucidating their findings. Notably, our study’s findings regarding Oscillosperaceae are contradictory to those reported by Yun et al (2023) , who documented an increase in Oscillospira among RA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a more severe disease course and unfavorable prognosis have been consistently associated with the female gender ( Finckh et al, 2022 ). Despite extensive research on gender-related distinctions in RA ( Di Florio et al, 2020 ; Favalli et al, 2019 ), Yun et al (2023) recently highlighted a lack of studies specifically examining the gut microbiome characteristics in females, elucidating their findings. Notably, our study’s findings regarding Oscillosperaceae are contradictory to those reported by Yun et al (2023) , who documented an increase in Oscillospira among RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research on gender-related distinctions in RA ( Di Florio et al, 2020 ; Favalli et al, 2019 ), Yun et al (2023) recently highlighted a lack of studies specifically examining the gut microbiome characteristics in females, elucidating their findings. Notably, our study’s findings regarding Oscillosperaceae are contradictory to those reported by Yun et al (2023) , who documented an increase in Oscillospira among RA patients. Consequently, our findings will contribute to a more comprehensive understanding of gender-specific variations in the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%